2021
DOI: 10.3390/biology10121319
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives on Chitinolytic Enzymes and Their Agro-Industrial Applications

Abstract: Chitinases are a large and diversified category of enzymes that break down chitin, the world’s second most prevalent polymer after cellulose. GH18 is the most studied family of chitinases, even though chitinolytic enzymes come from a variety of glycosyl hydrolase (GH) families. Most of the distinct GH families, as well as the unique structural and catalytic features of various chitinolytic enzymes, have been thoroughly explored to demonstrate their use in the development of tailor-made chitinases by protein en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 108 publications
1
34
0
1
Order By: Relevance
“…Very scarce literature deals with static liquid cultures for the production of chitinases, which are generally obtained in shaken (or stirred) cultures or in solid-state conditions [ 38 ]. In a couple of works, static cultures demonstrated to be more efficient than shaken cultures both for biomass and chitinase production by Aspergillus terreus and Alternaria alternata [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Very scarce literature deals with static liquid cultures for the production of chitinases, which are generally obtained in shaken (or stirred) cultures or in solid-state conditions [ 38 ]. In a couple of works, static cultures demonstrated to be more efficient than shaken cultures both for biomass and chitinase production by Aspergillus terreus and Alternaria alternata [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, maximum fungal chitinase production is observed at acidic or sub-acidic pH [ 38 ]. Chatterton and Punja [ 49 ] reported that the maximum chitinase activity by a soil strain of Clonostachys rosea f. catenulata was obtained at pH 6.0, with ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its high homology with human CHIA, monkey CHIA might potentially be adjusted for future purposes. For example, microbial chitinases have been used in a wide range of applications [55]. CHIA could therefore become a robust tool in chitooligosaccharide production for agricultural and biomedical purposes (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Nanoemulsion-based essential oils on the surface of fruits can prevent fungi (12) . Chitinase enzymes can also be utilised as a green alternative to antifungal chemical disinfectants because they can hydrolyse chitin present in the fungal cell wall (13) . Large scale applications of free chitinase to control postharvest decay by fungi are restricted due to the operational instability and thermal denaturation of the soluble form of the enzyme.…”
Section: In Vitro Antifungal Assaymentioning
confidence: 99%